A Comparison of Nonstaggered Compact FDTD Schemes for the 3D Wave Equation - Kowalczyk, Konrad; van Walstijn, M. (Proc. IEEE Int. Conf. on Acoustics, Speech, and Signal Processing (ICASSP), 2010)
This paper aims at providing a better insight into the 3D approximations of the wave equation using compact finite-difference time-domain (FDTD) schemes in the context of room acoustic simulations. A general family of 3D compact explicit and implicit schemes based on a nonstaggered rectilinear grid is analyzed in terms of stability, numerical error, and accuracy. Various special cases are compared and the most accurate explicit and implicit schemes are identified. Further considerations presented in the paper include the direct relationship with other numerical approaches found in the literature on room acoustic modeling such as the 3D digital waveguide mesh and Yee's staggered grid techniqu
LMS::939
Keywords: Acoustic propagation; acoustic signal processing; architectural acoustics; finite-difference time-domain (FDTD) methods

An acoustical zoom based on informed spatial filtering - Thiergart, Oliver; Kowalczyk, Konrad; Habets, Emanuël (Proc. Intl. Workshop Acoust. Echo Noise Control (IWAENC), 2014)
Keywords: microphone arrays; Spatial sound acquisition; Optimum beamforming

A Phase Grating Approach to Modeling Surface Diffusion in FDTD Room Acoustics Simulations - Kowalczyk, Konrad; van Walstijn, M.; Murphy, D. (IEEE Transactions on Audio Speech and Language Processing, 2011)
In this paper, a method for modeling diffusive boundaries in finite-difference time-domain (FDTD) room acoustics simulations with the use of impedance filters is presented. The proposed technique is based on the concept of phase grating diffusers, and realized by designing boundary impedance filters from normal-incidence reflection filters with added delay. These added delays, that correspond to the diffuser well depths, are varied across the boundary surface, and implemented using Thiran allpass filters. The proposed method for simulating sound scattering is suitable for modeling high frequency diffusion caused by small variations in surface roughness and, more generally, diffusers characterized by narrow wells with infinitely thin separators. This concept is also applicable to other wave-based modeling techniques. The approach is validated by comparing numerical results for Schroeder diffusers to measured data. In addition, it is proposed that irregular surfaces are modeled by shaping them with Brownian noise, giving good control over the sound scattering properties of the simulated boundary through two parameters, namely the spectral density exponent and the maximum well dept
LMS::938
Keywords: Acoustic refraction; acoustic scattering; acoustic signal processing; architectural acoustics; digital filters; finite-difference time-domain; FDTD; methods; fractals

Blind system identification using sparse learning for TDOA estimation of room reflections - Kowalczyk, Konrad; Habets, Emanuël; Kellermann, Walter; Naylor, Patrick A. (IEEE Signal Processing Letters, 2013)
Localization of early room reflections can be achieved by estimating the time-differences-of-arrival (TDOAs) of reflected waves between elements of a microphone array. For an unknown source, we propose to apply sparse blind system identification (BSI) methods to identify the acoustic impulse responses, from which the TDOAs of temporally sparse reflections are estimated. The proposed time-and frequency-domain adaptive algorithms based on crossrelation formulation are regularized by incorporating an l-norm sparseness constraint, which is realized using a split Bregman method. These algorithms are shown to outperform standard crossrelation-based BSI techniques when estimating TDOAs of reflections in the presence of background noise. © 1994-2012 IEE
Keywords: Blind system identification; Bregman method; crossrelation error; sparse learning; time delay estimation

Comparison of subspace-based and steered beamformer-based reflection localization methods - Mabande, Edwin; Sun, Haohai; Kowalczyk, Konrad; Kellermann, Walter (19th European Signal Processing Conference, EUSIPCO 2011, 2011)
This paper presents a comparative study of several techniques that are applicable to the localization of the most significant reflectors in an acoustic environment. It focuses on subspace-based and steered beamformer-based localization techniques and includes eigenbeam (EB)-ESPRIT, EBMUSIC, and EB-minimum variance distortionless response (EB-MVDR) methods. The directions of arrival (DOAs) of the sound sources and reflective surfaces in an acoustic environment are estimated from the acoustic images of rooms, which are obtained using a microphone array. The applicability of the presented methods in practice is confirmed by experimental results from real measurements. © 2011 EURASI

Diffuseness-based mixing time estimation using a spherical microphone array - Götz, P.; Silzle, A.; Kowalczyk, Konrad; Habets, Emanuël (Proc. of the International Conference on Spatial Audio, 2014)

Estimation of acoustic reflection coefficients through pseudospectrum matching - Markovic, D.; Kowalczyk, Konrad; Antonacci, Fabio; Hofmann, Christian; Sarti, A.; Kellermann, Walter (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2014)
Estimating the geometric and reflective properties of the environment is important for a wide range of applications of space-time audio processing, from acoustic scene analysis to room equalization and spatial audio rendering. In this manuscript, we propose a methodology for frequency-subband in-situ estimation of the reflection coefficients of planar surfaces. This is a rather challenging task, as the reflection coefficients depend on the frequency and the angle of incidence and their estimate is highly sensitive to background noise and interfering sources. Our method is based on the assumption that we know the geometry of the reflectors; the position and the radiation pattern of the source; the position and the spatial response of the array. Applying beamforming algorithms on a single set of measured sensor data, we estimate the angular distribution of the acoustic energy (angular pseudospectrum) that impinges on a microphone array. We then apply a two-step iterative estimation technique based on an Expectation-Maximization (EM) algorithm. The first step estimates the scaling factors. The second one infers the reflection coefficients from the scaling factors. Under the assumption of additive white Gaussian noise, we finally determine the reflection coefficients with a Maximum Likelihood (ML) estimation method. The effectiveness and the accuracy of the proposed technique are assessed through experiments based on measured dat
Keywords: algorithm; beamforming; expectation maximization; Microphone array; pseudospectrum matching; reflection coefficient; reverberation

Extended Kalman filter with probabilistic data association for multiple non-concurrent speaker localization in reverberant environments - Chakrabarty, Soumitro; Kowalczyk, Konrad; Taseska, Maja; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2014)
Acoustic source localization and tracking (ASLT) in reverberant environments is a challenging task due to the multi-path propagation of acoustic waves. ASLT is often based on the use of a Kalman filter or a particle filter, with time-difference-of-arrival (TDOA) estimates used as measurements. In this work, we aim to track non-concurrent speakers by applying an extended Kalman filter (EKF) with probabilistic data association (PDA) that takes into account multiple measurements simultaneously. By using PDA, the inaccuracy of the measurements caused by room reflections and noise is explicitly taken into account. Unlike in typical approaches where the measurements consist of broadband TDOA estimates, the measurements in the proposed approach consist of multiple narrowband direction-of-arrival (DOA) estimates obtained from distributed microphone arrays. Experimental results demonstrate that incorporating PDA and using properly selected narrowband DOA estimates leads to a better tracking performance, as compared to the standard EKF with a single narrowband or broadband measuremen
Keywords: extended Kalman filter; acoustic source localization; source tracking; recursive Bayesian filter

Finite Difference Time Domain Modeling of Phase Grating Diffusion - Kowalczyk, Konrad; van Walstijn, M. (Proceedings of the 4th International Symposium on Communications, Control and Signal Processing, ISCCSP 2010, 2010)
In this paper, a method for modeling diffusion caused by non-smooth boundary surfaces in simulations of room acoustics using finite difference time domain (FDTD) technique is investigated. The proposed approach adopts the well-known theory of phase grating diffusers to efficiently model sound scattering from rough surfaces. The variation of diffuser well-depths is attained by nesting allpass filters within the reflection filters from which the digital impedance filters used in the boundary implementation are obtained. The presented technique is appropriate for modeling diffusion at high frequencies caused by small surface roughness and generally diffusers that have narrow wells and infinitely thin separators. The diffusion coefficient was measured with numerical experiments for a range of fractional Brownian diffuser
LMS::940
Keywords: acoustic signal processing; acoustic scattering; acoustic refraction; architectural acoustics; digital filters; fractals

Generating virtual microphone signals in noisy environments - Habets, Emanuël; Craciun, Alexandra; Kowalczyk, Konrad (Proc. European Signal Processing Conf. (EUSIPCO), 2013)
Keywords: noise reduction; microphone arrays; spatial sound; parametric sound field model; Wiener filter

Joint DOA and TDOA estimation for 3D localization of reflective surfaces using eigenbeam MVDR and spherical microphone arrays - Sun, Haohai; Mabande, Edwin; Kowalczyk, Konrad; Kellermann, Walter (36th IEEE International Conference on Acoustics, Speech, and Signal Processing, ICASSP 2011, 2011)
Methods of 3D direction of arrival (DOA) estimation, coherent source detection and reflective surface localization are studied, based on recordings by a spherical microphone array. First, the spherical harmonics domain minimum variance distortionless response (EB-MVDR) beamformer is employed for the localization of broadband coherent sources, which is characterized by simpler frequency focusing matrices than the corresponding element-space implementation, and by a higher resolution than conventional spherical array beamformers. After the DOA estimation step, the source signals are extracted by EB-MVDRs. Then, by computing the crosscorrelation functions between the extracted signals, the coherent sources are detected and their time differences of arrival (TDOA) are estimated. Given the positions of the array and the reference source, and the estimated DOA and TDOA of the coherent sources, the positions of the major reflectors can be inferred. Experimental results in a real room validate the proposed method. © 2011 IEE
Keywords: DOA; localization of reflectors; spherical harmonics; Spherical microphone array; TDOA

Localization of distinct reflections in rooms using spherical microphone array eigenbeam processing - Sun, Haohai; Kellermann, Walter; Mabande, Edwin; Kowalczyk, Konrad (Journal of the Acoustical Society of America, 2012)
This paper presents an experimental and comparative study of several spherical microphone array eigenbeam (EB) processing techniques for localization of early reflections in room acoustic environments, which is a relevant research topic in both audio signal processing and room acoustics. This paper focuses on steered beamformer-based and subspace-based localization techniques implemented in the spherical EB domain, including the plane-wave decomposition, eigenbeam delay and sum, eigenbeam minimum variance distortionless response, eigenbeam multiple signal classification (EB-MUSIC), and eigenbeam estimation of signal parameters via rotational invariance techniques (EB-ESPRIT) methods. The directions of arrival of the original sound source and the associated reflection signals in acoustic environments are estimated from acoustic maps of the rooms, which are obtained using a spherical microphone array. The EB-domain-based frequency smoothing and white noise gain control techniques are derived and employed to improve the performance and robustness of reflection localization. The applicability of the presented methods in practice is confirmed by experiments carried out in real rooms. (C) 2012 Acoustical Society of America. [http://dx.doi.org/10.1121/1.368847

Mixing time prediction using spherical microphone arrays - Götz, P.; Kowalczyk, Konrad; Silzle, A.; Habets, Emanuël (Journal of the Acoustical Society of America, 2015)

On 2D localization of reflectors using robust beamforming techniques - Mabande, Edwin; Sun, Haohai; Kowalczyk, Konrad; Kellermann, Walter (36th IEEE International Conference on Acoustics, Speech, and Signal Processing, ICASSP 2011, 2011)
This paper presents a method for the localization of reflectors in an acoustic environment, using robust beamforming techniques and a cylindrical microphone array, for which an intuitive and highly efficient three-step procedure is proposed. First, the directions of arrival (DOAs) corresponding to the sound source and reflectors are estimated by a robust Minimum Variance Distortionless Response (MVDR) beamformer. Next, signals originating from the estimated DOAs are extracted by a robust superdirective beamformer, from which time differences of arrival (TDOAs) of major reflections are estimated by crosscorrelation analysis. Finally, by using additional information about the position of the direct sound source relative to the array, the positions of the reflective boundaries of the room can be inferred. Experiments based on real measurements carried out in a moderately reverberant room show the effectiveness of this method. © 2011 IEE
Keywords: Beamforming; Room Inference; Source Localization; TDOA Estimation

Parametric spatial sound processing: A flexible and efficient solution to sound scene acquisition, modification, and reproduction - Kowalczyk, Konrad; Thiergart, Oliver; Taseska, Maja; Del Galdo, Giovanni; Pulkki, Ville; Habets, Emanuël (IEEE Signal Processing Magazine, 2015)

Reflection coefficient estimation by pseudospectrum matching - Marković, D.; Hofmann, Christian; Antonacci, F.; Kowalczyk, Konrad; Sarti, A.; Kellermann, Walter (International Workshop on Acoustic Signal Enhancement (IWAENC), 2012)
This paper presents a novel model-based method for in-situ estimation of sound reflection coefficients in acoustic enclosures. The method uses a modeling engine for simulation of acoustic propagation and generation of the spatial pseudospectrum using a beamforming technique. The simulated pseudospectrum is matched with the measured pseudospectrum acquired by a real beamforming microphone array in order to estimate reflection coefficients of the walls of the acoustic enclosure. Experimental results confirm that the proposed method allows for an accurate estimation of the reflection coefficients, especially for reflective walls, typical of everyday environment
Keywords: Beamforming; Microphone array; Reflection coefficient estimation

Residual noise control using a parametric multichannel Wiener filter - Braun, Sebastian; Kowalczyk, Konrad; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2015)
Keywords: array processing; noise suppression; multichannel Wiener filter; residual noise control

Room Acoustics Simulation Using 3-D Compact Explicit FDTD Schemes - Kowalczyk, Konrad; van Walstijn, M. (IEEE Transactions on Audio Speech and Language Processing, 2011)
This paper presents methods for simulating room acoustics using the finite-difference time-domain (FDTD) technique, focusing on boundary and medium modeling. A family of nonstaggered 3-D compact explicit FDTD schemes is analyzed in terms of stability, accuracy, and computational efficiency, and the most accurate and isotropic schemes based on a rectilinear grid are identified. A frequency-dependent boundary model that is consistent with locally reacting surface theory is also presented, in which the wall impedance is represented with a digital filter. For boundaries, accuracy in numerical reflection is analyzed and a stability proof is provided. The results indicate that the proposed 3-D interpolated wideband and isotropic schemes outperform directly related techniques based on Yee's staggered grid and standard digital waveguide mesh, and that the boundary formulations generally have properties that are similar to that of the basic scheme use
LMS::937
Keywords: Acoustic propagation; acoustic reflection; acoustic signal processing; architectural acoustics; finite-difference time-domain (FDTD) methods; numerical analysis

Room geometry inference based on spherical microphone array eigenbeam processing - Mabande, Edwin; Kowalczyk, Konrad; Sun, Haohai; Kellermann, Walter (Journal of the Acoustical Society of America, 2013)
The knowledge of parameters characterizing an acoustic environment, such as the geometric information about a room, can be used to enhance the performance of several audio applications. In this paper, a novel method for three-dimensional room geometry inference based on robust and high-resolution beamforming techniques for spherical microphone arrays is presented. Unlike other approaches that are based on the measurement and processing of multiple room impulse responses, here, microphone array signal processing techniques for uncontrolled broadband acoustic signals are applied. First, the directions of arrival (DOAs) and time differences of arrival (TDOAs) of the direct signal and room reflections are estimated using high-resolution robust broadband beamforming techniques and cross-correlation analysis. In this context, the main challenges include the low reflected-signal to background-noise power ratio, the low energy of reflected signals relative to the direct signal, and their strong correlation with the direct signal and among each other. Second, the DOA and TDOA information is combined to infer the room geometry using geometric relations. The high accuracy of the proposed room geometry inference technique is confirmed by experimental evaluations based on both simulated and measured data for moderately reverberant rooms. © 2013 Acoustical Society of Americ

Sound acquisition in noisy and reverberant environments using virtual microphones - Kowalczyk, Konrad; Thiergart, Oliver; Craciun, Alexandra; Habets, Emanuël (Proc. IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2013)
Keywords: spatial filtering; microphone array processing; Wiener filtering; spatial sound recording

Spatial perception of virtual X-Y recordings - Kowalczyk, Konrad; Craciun, Alexandra; Dachmann, C.; Habets, Emanuël (2014 14th International Workshop on Acoustic Signal Enhancement, IWAENC 2014, 2014)
Keywords: microphone array processing; spatial filtering; spatial audio perception; spatial sound recording

The SCENIC project: Environment-aware sound sensing and rendering - Annibale, Paolo; Antonacci, Fabio; Bestagini, P.; Brutti, A.; Canclini, Antonio; Cristoforetti, L.; Habets, Emanuël; Filos, Jason; Kellermann, Walter; Kowalczyk, Konrad; Lombard, Anthony; Mabande, E.; et al. (Proc. of the 2nd European Future Technologies Conference and Exhibition, Procedia Computer Science, 2011)
The SCENIC project is aimed at making the environment become an integral part of the acoustic system. The goal is to boost the performance of arrays of speakers and microphones and, in some cases, to enable applications that would not be possible otherwise. This paper describes how this can be achieve
Keywords: environment-aware sound processing; microphone and speaker arrays; computational acoustics

The SCENIC project: Space-time audio processing for environment-aware acoustic sensing and rendering - Annibale, Paolo; Antonacci, F.; Bestagini, P.; Brutti, A.; Canclini, A.; Cristoforetti, L.; Habets, Emanuël; Filos, J.; Kellermann, Walter; Kowalczyk, Konrad; Lombard, A.; Mabande, Edwin; et al. (131st Audio Engineering Society Convention 2011, 2011)
SCENIC is an EC-funded project aimed at developing a harmonized corpus of methodologies for environmentaware acoustic sensing and rendering. The project focusses on space-time acoustic processing solutions that do not just accommodate the environment in the modeling process but that make the environment help towards achieving the goal at hand. The solutions developed within this project cover a wide range of applications, including acoustic self-calibration, aimed at estimating the parameters of the acoustic system; environment inference, aimed at identifying and characterizing all the relevant acoustic reflectors in the environment. The information gathered through such steps is then used to boost the performance of wavefield rendering methods as well as source localization/characterization/extraction in reverberant environment

Wideband and Isotropic Room Acoustics Simulation Using 2-D Interpolated FDTD Schemes - Kowalczyk, Konrad; van Walstijn, M. (IEEE Transactions on Audio Speech and Language Processing, 2010)
In this paper, a complete method for finite-difference time-domain modeling of rooms in 2-D using compact explicit schemes is presented. A family of interpolated schemes using a rectilinear, nonstaggered grid is reviewed, and the most accurate and isotropic schemes are identified. Frequency-dependent boundaries are modeled using a digital impedance filter formulation that is consistent with locally reacting surface theory. A structurally stable and efficient boundary formulation is constructed by carefully combining the boundary condition with the interpolated scheme. An analytic prediction formula for the effective numerical reflectance is given, and a stability proof provided. The results indicate that the identified accurate and isotropic schemes are also very accurate in terms of numerical boundary reflectance, and outperform directly related methods such as Yee's scheme and the standard digital waveguide mesh. In addition, one particular scheme-referred to here as the interpolated wideband scheme-is suggested as the best scheme for most application
LMS::936
Keywords: acoustic impedance; acoustic propagation; acoustic signal processing; architectural acoustics; digital filters; finite-difference time-domain (FDTD) methods